Use of Dexamethasone to Prevent Extubation Failure in Pediatric Intensive Care Unit: A Randomized Controlled Clinical Trial - Carvalho, Haroldo Teofilo de [UNESP]; Fioretto, Jose Roberto [UNESP]; Bonatto, Rossano Cesar [UNESP]; Ribeiro, Cristiane Franco [UNESP]; Martin, Joelma Gonçalves [UNESP]; Carpi, Mario Ferreira [UNESP] (Georg Thieme Verlag Kg, 2020)
Extubation failure is a common event in intensive care units. Corticosteroids are effective in preventing failure in adults, but no consensus has been reached on this matter in pediatrics. We assessed the efficacy of intravenous dexamethasone in mechanically ventilated children and adolescents for more than 48hours, with at least one risk factor for failure. Extubations were scheduled 24hours in advance when possible, and patients were randomly assigned into two groups: one group received a loading dose followed by up to four doses of dexamethasone, and the other group received no corticosteroids. Need for reintubation and length of stay in the pediatric intensive care unit were similar in both groups, and frequency of reintubation was 12.9%.
Keywords: children; extubation failure; dexamethasone